Advanced Computational Intelligence Paradigms in Healthcare - 2 - Vaidya, S.; Yoshida, Hiroyuki (Studies in Computational Intelligence,, 2007)
Computational intelligence paradigms offer many advantages in maintaining and enhancing the field of healthcare. This volume presents seven chapters selected from the rapidly growing application areas of computational intelligence to healthcare systems, including intelligent synthetic characters, man-machine interface, menu generators, analysis of user acceptance, pictures archiving and communication systems. This book will serve as a useful resource for the health professionals, professors, students, and the computer scientists, who are working on or interested in learning healthcare systems, to overview the current stat-of-the-art of diverse applications of computational intelligence to healthcare practice. .